Solve for x
x=-\frac{35-18y}{9\left(y-2\right)}
y\neq 2
Solve for y
y=-\frac{35-18x}{9\left(x-2\right)}
x\neq 2
Graph
Share
Copied to clipboard
3xy-6x+14=\frac{7}{3}+6y
Add 6y to both sides.
3xy-6x=\frac{7}{3}+6y-14
Subtract 14 from both sides.
3xy-6x=-\frac{35}{3}+6y
Subtract 14 from \frac{7}{3} to get -\frac{35}{3}.
\left(3y-6\right)x=-\frac{35}{3}+6y
Combine all terms containing x.
\left(3y-6\right)x=6y-\frac{35}{3}
The equation is in standard form.
\frac{\left(3y-6\right)x}{3y-6}=\frac{6y-\frac{35}{3}}{3y-6}
Divide both sides by 3y-6.
x=\frac{6y-\frac{35}{3}}{3y-6}
Dividing by 3y-6 undoes the multiplication by 3y-6.
x=\frac{18y-35}{9\left(y-2\right)}
Divide -\frac{35}{3}+6y by 3y-6.
3xy-6y+14=\frac{7}{3}+6x
Add 6x to both sides.
3xy-6y=\frac{7}{3}+6x-14
Subtract 14 from both sides.
3xy-6y=-\frac{35}{3}+6x
Subtract 14 from \frac{7}{3} to get -\frac{35}{3}.
\left(3x-6\right)y=-\frac{35}{3}+6x
Combine all terms containing y.
\left(3x-6\right)y=6x-\frac{35}{3}
The equation is in standard form.
\frac{\left(3x-6\right)y}{3x-6}=\frac{6x-\frac{35}{3}}{3x-6}
Divide both sides by 3x-6.
y=\frac{6x-\frac{35}{3}}{3x-6}
Dividing by 3x-6 undoes the multiplication by 3x-6.
y=\frac{18x-35}{9\left(x-2\right)}
Divide -\frac{35}{3}+6x by 3x-6.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}